Black rice anthocyanins alleviate hyperlipidemia, liver steatosis and insulin resistance by regulating lipid metabolism and gut microbiota in obese mice. Issue 20 (16th September 2021) - Song, Haizhao; Shen, Xinchun; Zhou, Yang; Zheng, Xiaodong
Abstract : Supplementation of black rice anthocyanins (BRAN) alleviated high fat diet-induced obesity, insulin resistance and hepatic steatosis by improvement of lipid metabolism and modification of the gut microbiota. Abstract : Hyperlipidemia, liver steatosis and insulin resistance are common metabolic diseases associated with obesity. The present study was designed to investigate the in vivo protective value of black rice anthocyanins (BRAN) on hyperlipidemia, liver steatosis and insulin resistance in mice with high-fat-diet (HFD)-induced obesity and elucidate the underlying mechanism. Specific pathogen-free male C57BL/6J mice (four weeks old, weighing 17.6–20.9 g) were randomly divided into three groups and fed with low-fat diet (LFD, 10% fat energy), HFD (45% fat energy), or HFD supplemented with BRAN by intragastric administration for 14 weeks. The obesity-related biochemical indices and hepatic gene expression levels were determined. 16S rRNA sequencing was used to determine the gut microbial changes induced by BRAN treatment. The results showed that the body weight gain, triglycerides, total cholesterol, steatosis scores and insulin resistance index in the BRAN group decreased by 24.69%, 29.83%, 28.08%, 46.67% and 40.42%, respectively, compared to the HFD group. Gene expression analysis indicated that BRAN treatment improved the gene expression profiles involved in lipid metabolism compared with the mice fed HFD alone. Moreover, BRAN treatment significantly altered the composition of the gut microbiota, which was closely correlated with the obesity-related biomarkers. In conclusion, this study demonstrated that dietary supplementation of BRAN protected from obesity-associated hyperlipidemia, hepatic steatosis and insulin resistance by influencing the gut microbiota and lipid metabolism.